Landscape and recreation evaluation of recreation and health-improving forests in the Left-Bank Ukraine - Мусієнко , С. І.; Тарнопільська , О. М.; Бондаренко , В. В.; Лук’янець , В. А.; Кобець , О. В.; Костяшкіна , Т. Д. (Forestry and Forest Melioration, 2022)
Introduction As the capacity of the recreational and health-improving forests has not been thoroughly studied, their effective use is limited. Therefore, the urgent task is to determine the ecological and social capacity of this category of forests, as well as to create conditions for the free development of entrepreneurship which would be based on the full use of the forest resources for recreational purposes. The latter will enable not only improving the conditions for the health, educational and cultural development of the population, but also a comprehensive use of the forest resources as well as an increase of the revenue in the forest industry. Materials and Methods The evaluation of the landscape and recreational capacity of the recreational and health-improving forests in Left-Bank Ukraine that are in permanent use by state-owned forestry enterprises subordinate to the State Forest Resources Agency of Ukraine was carried out using the materials of the "Forest Fund" database of the Ukrderzhlisproekt Production Association (as of 2017) and forest management materials (mensuration description of stands), based on the natural features of the area and the purpose of the forests. The research covered the forest fund of 84 state forest enterprises within 11 administrative regions. Results The recreational and health-improving forests of Left-Bank Ukraine involve 92 species, including non-forest-forming species and even shrubs. Pinus sylvestris L. stands occupy the largest area, namely 40.7% of the area of the forest plots covered with forest vegetation. Among them, pure stands prevail (60.2%). The second place goes to the stands of Quercus robur L., 38.8%; 19.2% among them are pure ones. The stands dominated by Robinia pseudoacacia L. cover 3.8% of the area, with 4.1% pure ones. Alnus glutinosa L. stands occupy 2.9%, 3.1% of them are pure. Fraxinus excelsior L. stands cover 2.8% with 0.3% pure ones: Betula pendula Roth. occupies 2.6% with 1.6% of pure stands. The rest of the tree species occupy much smaller areas. Recreational and health-improving forests in Left-Bank Ukraine are characterized by a relatively low degree of recreational load, as the mass recreation and intensive recreation areas are 54,425.0 ha (21.4%) and 17,294.0 ha (6.8%) respectively. The zone of extensive recreation is 182,844.1 hectares (71.8%). In terms of natural zones, recreational and health-improving forests retain the same ratios of functional areas. Conclusions The recreational and health-improving forests of Left-Bank Ukraine are characterized by a relatively low degree of recreational load. At that, the vast majority have the first degree of recreational digression. The average index of the stage of recreational digression in their mass recreation zones and intensive recreation zones makes 1.9. Thus, the recreational load is acceptable, as the natural complex does not lose its ability to self-renewal. 2 Figs., 6 Tables, 20 Refs.